Facilitating Collective and Inclusive Decision Making on Integrated Water Resources Management in Burkina Faso - CGIAR Challenge Program on Water and Food (2014)
In Burkina Faso, more than two-thirds of the population relies on rain-fed agriculture for food and income. However, scarce and insufficient water or irregular rainfall frequently puts farmers at risk of losing their crops. Climate change is making already variable rainfall less reliable. Yet all kinds of water users—farmers, fishers, livestock herders, domestic users, city dwellers, emerging industries–and ecosystems depend on access to water of the right quality, in the right quantity, and at the right time.